Fuzzy multi-model based adaptive predictive control and its application to thermoplastic injection molding - Li, Mingzhong; Yang, Yi; Gao, Furong; Wang, Fuli (Canadian journal of chemical engineering, 2001)
Many chemical processes are inherently nonlinear. A single linear model is ineffective for these processes. Several local linear models may be developed for different operating conditions. A combination of these local models, through a fuzzy logic representation, results in an overall model for a wider operation range. In this paper, on‐line improvements and a fuzzy multi‐model have been proposed for predictive control implementation. Firstly, assuming that the premises of the fuzzy rules keep their original structures, the linear parameters in the rule consequents are on‐line updated by a weighted recursive least squares algorithm at each sample interval. Secondly, a batch learning algorithm is proposed to tune the fuzzy rule premises using a competitive learning algorithm. The effectiveness of the proposed improvements is demonstrated with experimental applications to the filling velocity control of thermoplastic injection molding De nombreux procédés chimiques sont par nature non linéaires. Un modèle linéaire simple est donc inefficace pour ces procédés. Plusieurs modèles linéaires locaux peuvent ětre mis au point pour différentes conditions de fonetionnement. Une combinaison de ces modèles locaux, par une représentation en logique floue, peut donner un modèle global pour une gamme plus large de fonctionnement. Dans cet article, des améliorations en ligne et un multi‐modèle flou sont proposés pour la mise en place d'un contrǒle prédictif. Premièrement, en supposant que les prémissses des règles floues gardent leurs structures originales, les paramètres linéaires dans les conséquences des règles sont mises à jour en ligne par un algorithme de moindres carrés récurrents pondéré à chaque intervalle d'échantillon. Deuxièmement, on propose un algorithme d'apprentissage discontinu pour ajuster les premisses des règles floues à l'aide d'un algorithme d'apprentissage compétitif. L'efficacité des améliorations proposées est démontrée par des applications expérimentales du contrǒle de la Vitesse de remplissage en moulage par injection de thermoplastique